COHESION OF PROFESSIONAL WRITINGS AS FOUND IN THE JAKARTA POST - Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2014)
Coherence is a key concept for text comprehension and text clarity. One feature that contributes to coherence is cohesion which is realized in cohesive devices and metadiscourse markers. The current study is about cohesion in professional writings found in The Jakarta Post. Its purposes are to find out the cohesive devices and metadiscourse markers and to analyze how the cohesion significantly contributes to the coherence. The study is descriptive and qualitative in nature. The data are 4 professional writings taken from The Jakarta Post. The research results show that the average of the textual cohesion used in the professional writings is less than 50 %. It means that the textual cohesion is not sufficiently used. This also means that the cohesion used in the professional writings does not contribute so significantly to the texts’ coherence. Based on the conclusion above, it is suggested that the students be reminded the importance of textual cohesion to contribute coherence. The teacher should teach the students what textual and point-to-point cohesion is. Key words: cohesive devices, metadiscourse markers, textual cohesion, point-to-point cohesion